In Situ Pyrolysis Tracking and Real‐Time Phase Evolution: From a Binary Zinc Cluster to Supercapacitive Porous Carbon. Issue 32 (20th May 2020) - Wang, Yi‐Fan; Liang, Yiyu; Wu, Yan‐Fang; Yang, Jian; Zhang, Xu; Cai, Dandan; Peng, Xu; Kurmoo, Mohamedally; Zeng, Ming‐Hua
Abstract: The in situ tracking of the pyrolysis of a binary molecular cluster [Zn7 (μ3 ‐CH3 O)6 (L)6 ][ZnLCl2 ]2 is presented with one brucite disk and two mononuclear fragments (L=mmimp: 2‐methoxy‐6‐((methylimino)‐methyl)phenolate) to porous carbon using TG‐MS from 30 to 900 °C. Following up the spilled gas product during the decomposed reaction of zinc cluster along the temperature rising, and in conjunction with XRD, SEM, BET and other materials characterization, where three key steps were observed: 1) cleavage of the bulky external ligand; 2) reduction of ZnO and 3) volatilization of Zn. The real‐time‐dependent phase‐sequential evolution of the remaining products and the processing of pore forming template transformation are proposed simultaneously. The porous carbon structure featuring a uniform nano‐sized pore distribution synthesized at 900 °C with the highest surface area of 1644 m 2  g −1 and pore volume of 0.926 cm 3  g −1 exhibits the best known capacitance of 662 F g −1 at 0.5 A g −1 . Abstract : Supercharged : The in situ pyrolysis and real‐time progressive phase evolution of a binary zinc molecular cluster are tracked. The supercapacitive porous carbon, which is obtained under 900 °C, has a record capacitance of 662 F g −1 at 0.5 A g −1 .